Reproduction in Sepia aculeata Van Hasselt, 1835 along the Andhra Pradesh coast, off the western Bay of Bengal - Felix, Jasmin; Muktha Menon; Shubhadeep Ghosh; Latha Shenoy (Indian Journal of Fisheries, 2023)
Sepia aculeata Van Hasselt, 1835 is a commercially important cuttlefish in Indian seaswith limited studies on its biology from the Indo-Pacific region. This study, observed thereproductive biology of S. aculeata from samples landed by the trawl fishery operating offthe coast of north Andhra Pradesh, off the western Bay of Bengal. A total of 3511 sampleswere studied, of which 2241 were females having dorsal mantle length (DML) ranging from8.7 to 21.4 cm and weight from 78 to 901 g and 1260 were male specimens of DML rangingfrom 7.9 to 21.9 cm and weight from 54 to 738 g. Females dominated the landings with a sexratio of 1.78. The length at first maturity was estimated at 14.3 and 12.6 cm DML for femalesand males, respectively. Both sexes spawned throughout the year with two significant peaksfrom July to October and from December to February with minor intermittent peaks. Theabsolute fecundity ranged from 330±1.44 x 102 eggs, with a relative fecundity of 75±8.94 x102 eggs 100 g-1 body weight. The results of this study may be used as inputs in assessingthe stock of S. aculeata in the study region.Keywords:Cephalopods, Needle cuttlefish, Size at firstmaturity, Spawning season, Trawl fisheries